2015
DOI: 10.1128/iai.03158-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Passage Selects for Chlamydia muridarum with Enhanced Infectivity in Cultured Cells but Attenuated Pathogenicity in Mouse Upper Genital Tract

Abstract: bAlthough modern Chlamydia muridarum has been passaged for decades, there are no reports on the consequences of serial passage with strong selection pressure on its fitness. In order to explore the potential for Pasteurian selection to induce genomic and phenotypic perturbations to C. muridarum, a starter population was passaged in cultured cells for 28 generations without standard infection assistance. The resultant population, designated CMG28, displays markedly reduced in vitro dependence on centrifugation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 54 publications
2
74
0
Order By: Relevance
“…Both resulted in downstream frame shifts and premature determination codons in the gene coding for TC0412. Although different mutations in this gene from C. trachomatis were found to affect the infectivity of C. trachomatis in the mouse lower genital tract (39), mutations in this gene were shown to have no significant effect on either the infectivity or the pathogenicity of C. muridarum in the mouse genital tract (36). Both the G0.1.1 and G5-pGFP-Luci C. muridarum organisms were propagated in HeLa cells and purified as elementary bodies as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both resulted in downstream frame shifts and premature determination codons in the gene coding for TC0412. Although different mutations in this gene from C. trachomatis were found to affect the infectivity of C. trachomatis in the mouse lower genital tract (39), mutations in this gene were shown to have no significant effect on either the infectivity or the pathogenicity of C. muridarum in the mouse genital tract (36). Both the G0.1.1 and G5-pGFP-Luci C. muridarum organisms were propagated in HeLa cells and purified as elementary bodies as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…The immunofluorescence assays used for titrating live organisms were carried out as described previously (8,36,40). For titrating the live organisms recovered from a given sample, the mean number of inclusions per view was derived from counting five random views.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because a single inoculation of C. muridarum organisms in the mouse lower genital tract can cause hydrosalpinx and infertility (7)(8)(9), closely mimicking the tubal adhesion, hydrosalpinx, and infertility observed in women urogenitally infected with C. trachomatis (10)(11)(12). Although C. muridarum is not a natural sexually transmitted agent of mice, chlamydiologists have used this model not only to identify both chlamydial (13)(14)(15)(16)(17) and host (1,5,(18)(19)(20)(21)(22)(23)(24) pathogenic determinants but also to define the roles of ascending infection and tubal inflammation in chlamydial induction of hydrosalpinx (9,16,25,26). Nevertheless, questions such as how a self-limited infection with C. muridarum in the mouse genital tract can trigger tubal fibrosis or hydrosalpinx that lasts long after the tubal infection is resolved (9,25) remain unanswered.…”
mentioning
confidence: 99%
“…The exact percentage representation of the variants in both Nigg A and Nigg V has not been determined, although Jasper et al have presented a summary of important single nucleotide polymorphisms (SNPs) for Nigg A (32). Chen and colleagues have shown that a change in variant representation in C. muridarum can occur through in vitro passage (33). Therefore, we used these two populations to determine if disease outcome during infection with a population of variants is associated with expression of a given miRNA profile.…”
mentioning
confidence: 99%